De katolske bisper og reformationen i Danmark - Grell, Ole Peter (Kirkehistoriske Samlinger, 2012)
De sidste katolske bisper har fået et ringe eftermæle i dansk reformationshistorie: Ikke alene var de ikke opgaven voksen, men de var også moralskt dubiøse og teologisk og politisk inkompetente. Resutatet var at den katolske kirke i Danmark blev totalt overvældet af en fremstormende evangelisk bevægelse. I det følgende skal jeg forsøge at nuancere dette billede og rehabilitere de bisper, der aktivt forsøgte at bekæmpe den evangeliske bevægelse ikke uden succes specielt i årene fra 1526 til og med 1528. Summary This article considers the evangelical movement in Denmark seen from the perspective of the leaders of the Catholic church. The Danish bishops played a major part in the deposition of King Christian II in early 1523 and the election of his uncle Frederik I as his replacement. They made sure that the newly appointed king signed a coronation charter which not only guaranteed all the rights and privileges of the Catholic Church in Denmark, but also promised immediate Royal intervention against any evangelical preaching. Despite their political influence and unity in 1523 the bishops still felt the need to engineer a declaration from their lay colleagues within the Royal Council reaffirming their support for the pope and the Catholic Church only a little over a year later. Evidently the bishops had some serious concerns about the loyalty to the Catholic church of both their lay colleagues within the Council and the King. The lack of a papaly confirmed archbishop did not make the situation easier for the bishops and the Catholic church. That they refrained from taking any initiative to remedy this situation was to prove extremely damaging to the Catholic cause. Furthermore, when one of the two elected candidates for the archbishopric finally received papal confirmation in January 1526 the bishops proved unable to convince the other candidate, Aage Sparre, to vacate the seat, which he had occupied since his election. Encouraged and supported by king Frederik I Aage Sparre refused to back down thereby causing a damaging split within the episcopal college. Well in advance of the parliament (herredag) which met in 1526 the two most prominent and respected Catholic bishops, Ove Bille and Lage Urne, had realised that direct support for the Catholic church and intervention against the growing evangelical movement could no longer be expected from the king and the Council. They therefore decided personally to intervene against the evangelical preachers within their bishoprics using their legal powers. Their approach proved successful and was quickly emulated by other bishops such as Jørgen Friis in Viborg and the arche-electus in Lund, Aage Sparre. But where Sparre, despite not even being the rightful occupant of his see, was able to draw on the support of his lay colleagues within the Royal Council and make a success of his intervention against the evangelical preachers in the city of Malmø, Jørgen Friis failed abysmally in Viborg, lacking support from the local nobility as well as from his own chapter. Success clearly depended on the reputation and standing of the individual bishop. This might also explain why the bishop of Odense, Jens Andersen Beldenak, apart from his pastoral letter to the town of Assens in his own bishopric wrote another two pastoral letters to the towns of Viborg and Ålborg both in bishoprics where the incumbents were generally despised. These pastoral letters are the only instances we have of one of the Danish, Catholic bishops taking on the evangelical preachers theologically. The letter to Viborg in particular has been seen as proof that bishop Beldenak had come round to a Christian humanist position. There is, however, little if anything in the letter to support such a view. Instead, Beldenak argues for the traditional authority of the church, the churchfathers, and the use of the Vulgata Bible. He may well have shared this consiliarist position with the majority of his colleagues such as the bishop of Aarhus, Ove Bille. Bearing in mind the bishops’ reluctance to use the debating skills of the Christian humanist theologian Poul Helgesen when taking issue with the evangelical preachers in the late 1520s, because they had concerns about his theological position and view of the church and its leaders, it seems highly unlikely that Christian humanism should have appealed to any of the Danish bishops. The years between 1526 and 1528 proved decisive in the Catholic bishops’ attempt to halt or prevent the Reformation. Within their individual sees the bishops sought to combat the evangelical movement primarily through legal intervention, but occasionally also through theological involvement. Despite the constant political and religious pressure they found themselves under, confronted with a rapidly growing evangelical movement which was increasingly supported by the king, and with no assistance forthcoming from friends and family within the nobility, the bishops still achieved a measure of success. The death of bishop Lage Urne, the most respected and influential of the Catholic bishops, in the summer of 1529, however, weakend the episcopal college dramatically. This was aggravated by the retirement of the elderly bishop of Odense, Jens Andersen Beldenak, later that year. Their replacements, Knud Gyldenstjerne og Joachim Rønnow, were totally dependent on Frederik I for their promotion – they did not receive papal confirmation – and had to promise not to intervene against the evangelical preachers and their followers within their bishoprics. From 1532 the elected bishops who depended on the crown for their promotion were in the majority and a Reformation was only a question of time. The death of Frederik I in spring 1533, however, offered the Catholic bishops and their supporters a window of opportunity to turn the clocks back, which they grapped. However, the rebellion of the cities of Malmø and Copenhagen and the subsequent civil war guaranteed that this opportunity proved shortlived, and a Reformation resulted from Christian III’s victory in 1536. The bishops may not have had much to play for after the parliament of 1530, but between 1526 and 1528 they made a sustained effort to halt the progress of the evangelical movement, despite the lack of support they received from both the king and their noble colleagues within the Council. That they eventually lost the battle should not detract from the fact that they achieved some success in halting and delaying the reformation.